Doing Tolerance. Urban Interventions and Forms of Participation. - (:unkn) unknown (Barbara Budrich, 2020)
How is tolerance reflected in urban space? Which urban actors are involved in the practices and narratives of tolerance? What are the limits of tolerance? The volume answers these questions by considering different forms of urban in/exclusion and participatory citizenship. By drawing together disparate yet critical writings, Doing Tolerance examines the production of space, urban struggles and tactics of power from an interdisciplinary perspective. Illustrating the paradoxes within diverse interactions, the authors focus on the conflict between heterogeneous groups of the governed, on the one hand, and the governing in urban spaces, on the other. Above all, the volume explores the divergences and convergences of participatory citizenship, as they are revealed in urban space through political, socio-economic and cultural conditions and the entanglements of social mobilities.
Keywords: Stadtgesellschaft; Toleranz; Partizipation; Randgruppe; Bürgerbewegung; Protestbewegung; Rassismus; Einwanderer; Ausgrenzung; Stadtraum; Öffentlicher Raum; Raumnutzung; Heterogenität; Konfliktpotential; Machtstruktur